Citizen Science for Assessing Landscape Change - Cardille, Jeffrey A.; Jackson, Michelle M. (Learning Landscape Ecology, 2017)
Citizen science is increasingly recognized as a powerful tool for addressing ecological problems across large areas. Although not a new phenomenon, certain types of citizen science rely on advanced web-based technology not previously available. “Crowdsourcing” refers to a type of citizen science in which large data-collection tasks are allocated to volunteers using the Internet. Such tasks may require minimal time or effort on the part of the volunteer but—when combined with the efforts of many others—can produce enormous datasets that are extremely useful in research and monitoring. By encouraging public participation from people who may not be experts in a given scientific subject, crowdsourcing citizen science aims to gather and collate useful scientific information from a larger number of individuals than would otherwise be feasible. In this lab, you will participate in a crowdsourcing project and explore some of the basic components of citizen science as it can be applied to landscape ecology. This lab is designed to enable students to.